Pushing the Limits - McGarry, Katie (Australia Harlequin Teen, 2012)
No one knows what really happened the night Echo Emerson went from popular girl with jock boyfriend to gossiped-about outsider with "freaky" scars on her arms. Even Echo can't remember the whole truth of the horrible night that changed her life forever. But when Noah Hutchins, the smoking-hot loner in the black leather jacket, explodes into her life with his tough attitude and surprising understanding, Echo's world shifts in ways she could never have imagined. Yet the crazy attraction between them refuses to go away. And now Echo has to ask herself just what she'll risk for the one guy who might teach her how to love again ... Suggested level: secondary.
Keywords: Life change events -- Memory -- Teenagers